'Collinsella provencensis' sp. nov., 'Parabacteroides bouchesdurhonensis' sp. nov. and 'Sutterella seckii, ' sp. nov., three new bacterial species identified from human gut microbiota. (May 2018) - Dione, N.; Ngom, I.I.; Valles, C.; Cadoret, F.; Fournier, P.E.; Raoult, D.; Lagier, J.C.
Abstract: We report here the main characteristics of 'Collinsella provencensis' strain Marseille-P3740 (CSUR P3740), 'Parabacteroides bouchesdurhonensis' strain Marseille-P3763 (CSUR P3763) and 'Sutterella seckii' strain Marseille-P3660 (CSUR P3660), which were isolated using culturomics from the human gut microbiota of healthy individuals living in Marseille.